A hybrid wind energy harvester based on a double-rotor reverse synergy mechanism for high-speed railway. (March 2023) - Zhou, Xianzheng; Dai, Chutian; Liu, Genshuo; Tan, Xing; Zhang, Zutao; Pan, Yajia; Pan, Hongye; Ahmed, Ammar
Highlights: A hybrid wind energy harvester (HWEH) is proposed for high-speed railway. Double-rotor reverse synergy mechanism improves energy harvesting efficiency. The slip ring realizes the relative speed of the electromagnetic module magnet cutting the coil. Parallel connection of PVDF increases the charge output of piezoelectric module. The maximum energy output power of the system at the wind speed of 9 m/s is 394 mW. Abstract: With the growing expansion of high-speed railway, the power supply have become increasingly crucial. This research proposes a HWEH to power sensors and small electrical devices along the railroad. The four primary components of the HWEH: the parallel piezoelectric module, the electromagnetic synergy module, and the electric energy storage module. The HWEH uses the a double-rotor reverse synergy mechanism to achieve reverse rotation under wind drive. A conductive slip ring is incorporated. Increasing the relative speed of the disks furnished with magnets and coils improves the electromagnetic module's energy harvesting efficiency. The speed of the magnet disk and coil disk connected with the slip ring are increased. The power storage module converts the generated alternating current into direct current, which is then stored in the supercapacitor and used to power the railway monitoring sensor. The performance of the system is tested through simulation and experimentation. Compared with a single rotor, the efficiency of HWEH is improved by 34%. When the wind speed is 9 m/s, the output power of the HWEH is 394 mW. According to the findings of experiments, the HWEH has a high energy generation performance and can power sensors and other small electrical equipment along the railroad.